HEALTH MANAGEMENT OF NILE TILAPIA (Oreochromis niloticus) IN GROW-OUT PONDS AT BALAI BENIH IKAN (BBI) BATU KUMBUNG LINGSAR, WEST LOMBOK - Irnia Anggilia; Septiana Dwiyanti (Universitas Mataram, 2025)
Nile tilapia (Oreochromis niloticus) is one of the most important freshwater aquaculture commodities in Indonesia due to its rapid growth, high adaptability, and stable market demand. The success of cultivation is strongly influenced by proper health management, including water quality control, feed management, and disease prevention. This field practice was carried out at the Batu Kumbung Fish Hatchery (BBI), Lingsar, West Lombok, aiming to observe and understand health management practices in tilapia grow-out ponds. Data were collected through observation, interviews, documentation, and active participation in pond preparation, stocking, feeding, health monitoring, and harvesting. The results showed that water quality parameters were within optimal ranges (temperature 26.3–27.3°C; dissolved oxygen 5–7 mg/L; pH 7.5–8), feed conversion ratio (FCR) was 1.1, survival rate (SR) reached 80%, and selection index (IS) was 0%, indicating no disease cases during cultivation. These findings confirm that the implementation of appropriate health management effectively maintains fish health, reduces mortality, improves feed efficiency, and supports sustainable tilapia aquaculture. Tilapia health management in the BBI Batu Kumbung rearing pond, Lingsar, West Lombok, is carried out through pond preparation, water quality control, regular feeding, and disease prevention by administering Lugol and soaking the fish in a salt solution or PK (Potassium Permanganate).